KINAS, TEKSTAS IR FILOSOFIJA - Čepulis, Nerijus (Problemos, 2014)
Nerijus Milerius (sudarytojas), Audronė Žukauskaitė, Jūratė Baranova, Kristupas Sabolius, Lukas Brašiškis. Kinas ir filosofija: Kolektyvinė monografija.Vilnius: Vilniaus universiteto leidykla, 2013. 224 p. ISBN 978-609-459-228-7Film, Text and PhilosophyNerijus Čepulis